Evaluation of traditional and residual momentum strategies during the Covid period on the Johannesburg Stock Exchange - Yengwa, Mphathi Lubabalo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Traditional momentum is a concept which was first discovered by Jegadeesh and Titman (1993), defined as a tendency of stocks to experience a continuation in their relative performance. A stock that performed relatively well will continue to perform relatively well, and vice versa. It has been observed by other researchers that during market crises, traditional momentum tends to produce large negative returns for investors, defined as a momentum crash. To mitigate momentum crashes, many researchers have developed new momentum strategies which have better performance than traditional momentum during market crises; such strategies include residual momentum. While both residual and traditional momentum have been studied in international markets and locally, the performance of both the residual and traditional momentum strategies have not been examined in the most recent Covid-fuelled financial crisis on the Johannesburg Stock Exchange. The study compares the performance of hypothetical long-only winner traditional and residual momentum portfolios (from 2018"“2022) using various risk metrics, which include the tracking error, Sharpe ratio, Jensen's alpha and information ratio. To compare the statistical significance of the difference in mean returns of residual and traditional momentum strategies to the benchmark (FTSE/Johannesburg Stock Exchange (JSE) Top 40) the study uses Welch's t-test. The study uses an Auto regressive distributed lag (ARDL) regression to examine the effect that various market conditions (bull market, bear market and extreme volatility) have on the returns of residual and traditional momentum strategies. Given the limited period examined in this study, the Monte Carlo simulation was used to extrapolate potential outcomes of how the momentum strategies might perform under different market conditions (as mentioned) in 1 000 iterations of each condition. The simple return analysis undertaken in this research revealed that traditional momentum outperformed residual momentum both before and throughout the COVID period. In the risk-adjusted performance measures, traditional momentum outperformed at all four risk indicators during the 2020 COVID year. The statistical significance tests, which compared the strategies' mean returns to the benchmark, demonstrated no statistically significant difference in returns over the COVID year. Furthermore, when evaluating the strategies over a five-year period (2018-2022), the difference in mean returns was shown to be statistically insignificant. However, statistical significance in returns was shown in some individual years. The ARDL regression findings show that bull, bear, and volatility factors explain relatively little of the returns for both momentum strategies, which is consistent with previous research. The Monte Carlo simulation, using the bear variable, forecasted that traditional momentum would result in negative returns during market declines, but residual momentum would provide positive returns and surpass traditional momentum with a probability of 26%. When using the bull variable, the simulation discovered that both traditional and residual momentum strategies resulted in positive returns. However, the residual momentum strategy outperformed in terms of returns and had an 84% likelihood of outperforming the traditional momentum strategy across 1,000 iterations. Nevertheless, when the simulation included the volatility variable, it projected negative returns for residual momentum and positive returns for traditional momentum. Additionally, it estimated a 14% probability of residual momentum surpassing traditional momentum under volatile market circumstances.
Keywords: Efficient market theory; Residual momentum; Economic crisis; Johannesburg Stock Exchange; COVID-19 Pandemic, 2020-2023 -- Influence